Exploring air quality and health effects during diwali: A comprehensive study in Lucknow city - Suleman (Acta Geographica Debrecina Landscape & Environment series, 2025)
Diwali, a revered cultural festival nationwide, poses significant environmental challenges, especially in urban hubs like Lucknow. Traditionally marked by elaborate rituals and widespread firecracker usage, Diwali contributes notably to air pollution. Amid mounting concerns over environmental degradation's health impacts, this study examines Diwali's air pollution dynamics, indoor exposure factors, and health effects in Lucknow. By dissecting these intricacies, it seeks to inform targeted interventions for environmental preservation and community health enhancement. The study adopts an exploratory survey design, employing both primary and secondary data collection methods. Primary data, acquired through structured questionnaires, involves 523 parents and 179 doctors in Lucknow, Uttar Pradesh. Quota and purposive sampling techniques were utilised to select participants meeting specific criteria. Statistical analyses, including frequency, Chi-square, and exploratory factor analysis, were conducted using SPSS version 25 to achieve research objectives. The results of the Diwali 2023 air pollution survey in Lucknow City indicate a significant rise in PM10 and PM2.5 levels, notably during nighttime, attributed to firecracker burning. Slight increases in SO2 and NO2 suggest additional fuel combustion. Further, hypotheses testing associations between locality types and indoor air pollution sources revealed significant links to factors like burning mosquito repellents, candles, and genetic predispositions. Doctors highlighted children in flats/apartments, aged 0-4, as most vulnerable, citing socioeconomic and behavioural influences. Seasonal variations and festivals, particularly Diwali, exacerbate air pollution effects. Doctors noted diverse health impacts, from respiratory issues to neurological effects, stressing the need for comprehensive mitigation efforts.